26 Meta-analysis comparing influence of no adjuvant treatment, postoperative radiotherapy and/or chemotherapy on survival in patients after primary surgery including lymphadenectomy for early stage uterine carcinosarcoma. (13th November 2020) - Student, V; Garzon, S; Prokop, L; Murad, MH; Sedlakova, I; Mariani, A
Abstract : Introduction: Uterine carcinosarcoma (UCS, malignant mixed Müllerian tumor) is rare but aggressive form of endometrial cancer according to metastatic potential. Standard treatment is primary surgery. Adjuvant therapy improves survival in advance disease but its benefit remains unclear in stage I (FIGO 2009). Methods: A systematic review and meta-analysis to compare influence of no adjuvant treatment (No AT) ± postoperative vaginal brachytherapy (VBT), adjuvant external beam radiation therapy (EBRT) ±VBT, adjuvant chemotherapy (CT) ±VBT, and adjuvant CT + EBRT±VBT on survival in patients with stage I UCS after primary surgery including at least hysterectomy, bilateral salpingo-oophorectomy, and lymphadenectomy. Prospectively stated selection criteria, data collection and comprehensive search strategy was registered on PROSPERO. Investigators independently extracted data. Random-effects meta-analysis was used to estimate risk ratios (RR). Results: We included 14 retrospective observational studies with 1, 090 UCS patients (figure 1 ). No AT±VBT was associated with higher mortality and recurrence compared to CT±VBT and compared to CT+EBRT±VBT; but no significant difference from EBRT±VBT. Both, CT±VBT and CT+ EBRT±VBT, had significantly lower mortality and recurrence compared to EBRT±VBT. There was higher mortality associated with CT±VBT compared to CT+EBRT±VBT. Heterogeneity was minimal in all analyses; however, none of these comparisons were randomized and the estimates were imprecise due to the small number of events (figure 2 ). Conclusion/Implications: Adjuvant chemotherapy appears to be effective in controlling recurrences and reduce mortality in early stage UCS.